Annual of Architecture (Atrium, 1989)
Estudios monográficos de la obra de diversos arquitectos: M.A. Arnaboldi; D. Benini; N.L. Berghof; R. Bofill; M. Borowski; M. Botta; C.F. Brullmann; A. Lavergnolle; C. Brodski; S. Calatrava; G. Casani; I. Docavo; A. Más Tomás; E. Gil Benso; N. Cinnamond; M. Cohen; J. Pesman; G. Coll Pons; A. Cruz Villalón; P. Chaix; J. P. Morel; R. de la Hoz Castanys; C. de Portzamparc; C. Dini; U. Capelli; C. Duarte; J. Lamas; A. Duarte Silva; N. Leónidas; F. Dusapin; F. Leclercq; E. Evans; D. Shalev; H. Fernández Martín; C. Ferrater; S. Fiszer; H. Gaudin; E. Giselbrecht; N. Grimshaw; P.L. Hansen; y otros.